The Term (Ridiculed) and Its Derivatives in the Holy Qur’an: An objective Study - Mohieldin, Imad Sarkol (Journal of Tikrit University for Humanities, 2022)
The following things were mentioned in the research: * The verses concerned with the research are nine verses of the Qur’an. * Avoid making fun of others. * Muslims are not safe from the tongue of the hypocrites in all cases. * The consequence of denying the religion of Allah Almighty and mocking Allah’s Messengers (peace be upon them) is dire, as the doom and torment of the deniers and cynics is inevitably descending upon them. * Ridicule, mockery, and belittling of others are enough to distract Muslims from their religion, morals and traditions that they inherited from the people of piety, as they have devastating effects in the Islamic society, which led to successive defeats at all levels. * Among the Islamic etiquette is for a Muslim to be called by the most beloved names, nicknames, or nicknames to his heart, as Allah Almighty has prohibited name-calling and calling others with what he dislikes from * The real strength of the Islamic community lies in the hearts of the honest and sincere among them, and not in deceptive appearances, since the first core of Islam were weak people like our master Ammar, Suhaib, Bilal and Khabab bin Al-Arit. *Faith, regret and repentance are of no benefit when witnessing torment. * Indeed, Allah is the defender of those who believe in Him, and He supports them against His enemies, and He is responsible for repelling evil from His righteous servants. * Allah Almighty will reward the pious believers on the Day of Resurrection with the best and most abundant reward, so He will enter them into the abode of peace in peace, and He will humiliate and shame their mocking enemies, so He will enter them into the lowest level of Hellfire (Allah forbid) * The people of falsehood have always wanted to ridicule preachers, scholars and believers.